2020
DOI: 10.9734/jpri/2020/v32i2130753
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Enrofloxacin and Ciprofloxacin Residues in Chicken Meat by High-Performance Liquid Chromatography

Abstract: Enrofloxacin and Ciprofloxacin antibiotics are widely used in chicken production for prophylaxis and therapeutics purposes. Existence of these antibiotic residues in chicken meat can pose hazards to human health. The present study was aimed to assess the residue level of these antibiotics in chicken meat. Chicken meat samples (including muscle, liver, kidney and fat) from poultry farms and retail market were collected. High Performance Liquid Chromatography (HPLC) was used for screening of enrofloxacin and cip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…In this study, tetracycline and doxycycline were not detected in all samples, which is consistent with the findings of another study conducted in Ethiopia that reported none of the samples had a detectable tetracycline and doxycycline residues. 18 However, the current findings are lower than those reported in India 37 which found about 18.89% and Tanzania 38 reported 35% of samples positive for oxytetracycline.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In this study, tetracycline and doxycycline were not detected in all samples, which is consistent with the findings of another study conducted in Ethiopia that reported none of the samples had a detectable tetracycline and doxycycline residues. 18 However, the current findings are lower than those reported in India 37 which found about 18.89% and Tanzania 38 reported 35% of samples positive for oxytetracycline.…”
Section: Discussioncontrasting
confidence: 64%
“…7 The study conducted in India reported a higher prevalence, which accounted for 33%. 37 The variation may be related to the types of samples analyzed to determine antibiotics, the latter being used in seafood. However, the study conducted in Tanzania reported that none of the samples contaminated with oxytetracycline exceeded MPL.…”
Section: Discussionmentioning
confidence: 99%
“…(2018 ) discovered ciprofloxacin residues with a mean of 24.8 ± 23.5. Verma et al . (2020 ) looked for ciprofloxacin residues in the muscle, liver, kidney, and fat of broiler chickens but found none in the gizzard, muscle, or heart.…”
Section: Discussionmentioning
confidence: 99%
“…These statistics underscore the substantial reliance on antibiotics within the Indian food-animal sector, posing a significant risk of promoting the emergence and spread of resistance among pathogens ( 12 ). These resistance pathogens have the potential to traverse from animals to humans and the environment through a variety of routes, including direct contact, the presence of antimicrobial residues in food products ( 13 , 14 ), and contamination originating from agricultural waste ( 4 ).…”
Section: Introductionmentioning
confidence: 99%